Histological changes in lung tissues related with sub-chronic exposure to ambient urban levels of PM2.5 in Córdoba, Argentina - Tavera Busso, Iván (2017)
Concentration of fine particulate matter (PM2.5) is one of the most important environmental parameters to estimate health impacts attributable to air pollution. Despite the fact there are many studies regarding PM2.5 effects on human health, most of them were performed under conditions that do not simulate the natural particles interaction with the organism. In the present paper, we studied the effects of mammals’ sub-chronic exposure to PM2.5 on the lower respiratory tract, addressing realistic exposure conditions to normal urban air. Thus, we exposed Wistar rats under controlled settings to the same normal urban air, with and without particles. Next, we analyzed chemical composition of PM2.5 and lungs samples, performed a histologic examination and run the comet assay to assess genotoxic effects. We found a strong agreement between lung tissues and PM2.5 elemental composition suggesting that metals found in lungs came from the particles inhaled. Histological analysis showed a mild to moderate infiltration, with a reduction of alveoli lumen and increment of alveolar macrophages and periodic acid-Schiff (PAS) (+) cells in treated animals. We also observed an increase in the number of nuclei with comets, mostly comets type 3, with a high DNA fragmentation as well. These results provide strong evidence that sub-chronic exposure to low particle levels, even below the 24 h WHO standard, can cause injuries in lungs tissues and DNA damage, as well.